Evaluasi Implementasi Single-Used Expandable Strategy Dan Dampak Lingkungan Terhadap Rantai Pasok Dan Logistik Palet Pada PT. Sumber Rezeki Palletindo - Sarah Hersa Amira (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to analyze the relationship of single-used expendable strategy and its impact on the environment on the supply chain and pallet logistics at PT. Sumber Rezeki Palletindo. There are two types of data used in this study, namely primary data by conducting in-depth interviews with employees of PT. Sumber Rezeki Palletindo and secondary data taken from previous research journals, the government's official website, namely the Agricultural Quarantine Agency. The results of this study indicate that the single-used expendable strategy used by PT. Sumber Rezeki Palletindo is considered the most effective because the costs incurred from production to product distribution are the most minimal costs compared to other strategies. As an implementation of green operation on pallets, the ISPM#15 fumigation process, Phosphine gas can be an alternative to fumigation in place of Methyl Bromide gas because it is considered not to leave residues harmful to the environment. Unfortunately, there is no alternative to Heat Treatment measures to reduce the environmental impact.